Aestivation Induces Changes in the mRNA Expression Levels and Protein Abundance of Two Isoforms of Urea Transporters in the Gills of the African Lungfish, Protopterus annectens - Chng, You R.; Ong, Jasmine L. Y.; Ching, Biyun; Chen, Xiu L.; Hiong, Kum C.; Wong, Wai P.; Chew, Shit F.; Lam, Siew H.; Ip, Yuen K. (Frontiers in Physiology, 2017)
The African lungfish, Protopterus annectens, is ammonotelic in water despite being ureogenic. When it aestivates in mucus cocoon on land, ammonia is detoxified to urea. During the maintenance phase of aestivation, urea accumulates in the body, which is subsequently excreted upon arousal. Urea excretion involves urea transporters (UT/Ut). This study aimed to clone and sequence the ut isoforms from the gills of P. annectens, and to test the hypothesis that the mRNA and/or protein expression levels of ut/Ut isoforms could vary in the gills of P. annectens during the induction, maintenance, and arousal phases of aestivation. Two isoforms of ut, ut-a2a and ut-a2b, were obtained from the gills of P. annectens. ut-a2a consists of 1227 bp and codes for 408 amino acids with an estimated molecular mass of 44.7 kDa, while ut-a2b consists of 1392 bp and codes for 464 amino acids with an estimated molecular mass of 51.2 kDa. Ut-a2a and Ut-a2b of P. annectens had a closer phylogenetic relationship with Ut/UT of tetrapods than Ut of fishes. While the mRNA expression pattern of ut-a2a and ut-a2b across various tissues of P. annectens differed, the transcript levels of ut-a2a and ut-a2b in the gills were comparable, indicating that they might be equally important for branchial urea excretion during the initial arousal phase of aestivation. During the maintenance phase of aestivation, the transcript level of ut-a2a increased significantly, but the protein abundance of Ut-a2a remained unchanged in P. annectens gills. This could be an adaptive feature to prepare for an increase in the production of Ut-a2a upon arousal. Indeed, arousal led to a significant increase in the branchial Ut-a2a protein abundance. Although the transcript level of ut-a2b remained unchanged, there were significant increases in the protein abundance of Ut-a2b in P. annectens gills throughout the three phases of aestivation. The increase in the protein abundance of Ut-a2b during the maintenance phase could also be an adaptive feature to prepare for efficient urea excretion when water becomes available.